KUALITAS HADIS LARANGAN MEMINANG DI ATAS PINANGAN ORANG LAIN - Zakiyah; Islamiyah (DIRAYAH : Jurnal Ilmu Hadis, 2021)
The purpose of this study is to reveal the hadith that prohibits proposing to someone else's proposal and the quality of the hadith. A woman who has been asked for a proposal cannot be proposed to another man because it can cause enmity between the two suitors. However, the existence of a proposal to a woman who has been proposed to another man does not make the marriage void, because the khitbah is not a legal requirement of marriage. This study aims to examine the hadith related to the prohibition of proposing to women on the proposal of others, the hadith that will be studied is the hadith narrated by Abu Daud. The method used in this research is descriptive qualitative by using library research. The researcher traced the rijal hadith books to find the quality of the hadith narrators narrated by Abu Daud. When viewed from the aspect of the muttashilan of the sanad, the hadith narrated by Abu Daud is continued and all the narrators, including the tsiqah narrators, are not found by any scholar who plundered them.